Gold catalysis in total synthesis - recent achievements - Pflästerer, Daniel; Hashmi, A. Stephen K. (Chemical Society reviews, 2015)
In this critical review the applications of gold catalysed reactions in total synthesis during the years since our last article are reviewed. At the end of this article a literature analysis is conducted to evaluate the progress in this field.